Error Correction Caused by the Deviation of the Center and the Swash of the Divided Disk Using Multihead Method - Bui, Quoc Thu; Nguyen, Van Vinh; Vu, Khanh Xuan (Old Journal, 2017)
The article presents a method to correct the error caused by the deviation of the center, the swash of the divided disk of the instrument that created full circle standard angles using multihead method. This instrument includes incremental coding divided disk with 10800 graduations, on which installed 6 sensor heads that is arranged into 2 arrays: one is 90^° interval of 4 heads and another is 120^° interval of 3 heads, which integrates the 2^10 bit interpolation. With the use the equal division average method (EDA), from the data obtained on the head, the instrument can correct the error caused by the eccentricity and swash of the divided disk. The achieved result is the error of the instrument being ±0.37, meet the requirements of the national metrology standard of the angular field.